2010
DOI: 10.4103/0970-1591.74457
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric extracorporeal shock wave lithotripsy: Predicting successful outcomes

Abstract: Extracorporeal shock wave lithotripsy (ESWL) is currently a first-line procedure of most upper urinary tract stones <2 cm of size because of established success rates, its minimal invasiveness and long-term safety with minimal complications. Given that alternative surgical and endourological options exist for the management of stone disease and that ESWL failure often results in the need for repeat ESWL or secondary procedures, it is highly desirable to identify variables predicting successful outcomes of ESWL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 36 publications
1
12
0
2
Order By: Relevance
“…Our analysis revealed that factors lowering the treatment success rate were stone multiplicity and large size (>10 mm), as expected from the results of previous reports [15,23]. When patients with multiple stones were excluded, three patients did not achieve success within three ESWL sessions.…”
Section: Discussionsupporting
confidence: 83%
“…Our analysis revealed that factors lowering the treatment success rate were stone multiplicity and large size (>10 mm), as expected from the results of previous reports [15,23]. When patients with multiple stones were excluded, three patients did not achieve success within three ESWL sessions.…”
Section: Discussionsupporting
confidence: 83%
“…Urinary stone disease in children is not an uncommon problem [ 1 ], which is likely recur due to many causes including metabolic disorders and congenital anatomical abnormality in the urinary tract [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extracorporeal shock wave lithotripsy (ESWL) has altered the treatment of upper tract stones in children [1]. Extracorporeal shock wave lithotripsy is harmless, safe and effective with excellent stone clearance rates in children [2-4].…”
Section: Introductionmentioning
confidence: 99%